(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recent business models are based on the latest information and telecommunication technologies cross over the world. Such approach allows global and local companies to become more competitive. Highlighted innovative trends successfully combine mobile messaging services - messengers, which become the main driver of the digital economy growth due to simplicity, convenience, safety and security, as well as a large number of users. Recent studies show the influence of some factors from the institutional environment of the business on the commercial success, especially in the period of COVID19. But to conduct a full assessment of the impact of the institutional environment on mobile messengers, the study of the influence of this factor alone is not enough. The research paper conducts a study of the influence of the institutional environment on the Telegram messenger, identifies the influence of the level of freedom on the messenger audience, analyze the relationship between the volume of the e-commerce market and the number of messenger users. Using correlation analysis, comparative study and statistical data authors investigate recent trends in messenger’s development; define the role of online messengers in internet marketing, including e-commerce; present case study of Telegram messenger in Russian market, and provide recommendations for messenger future development.